Patterns of co-occurring birth defects among infants with hypospadias. Issue 1 (February 2021) - Ludorf, Katherine L.; Benjamin, Renata H.; Navarro Sanchez, Maria Luisa; McLean, Scott D.; Northrup, Hope; Mitchell, Laura E.; Langlois, Peter H.; Canfield, Mark A.; Scheuerle, Angela E.; Scott, Daryl A.; Schaaf, Christian P.; Ray, Joseph W.; et al.
Summary: Introduction: Hypospadias, one of the most common male genital birth defects, occurs in 1 out of every 200 male births in the United States and is increasing in prevalence globally. Objective: This study aimed to characterize the combinations of birth defects that co-occur with hypospadias more often than expected by chance, while accounting for the complex clustering patterns of congenital defects. Study design: We analyzed cases with hypospadias and at least one additional co-occurring defect from the Texas Birth Defect Registry born between 1999 and 2014. For each combination, we calculated adjusted observed-to-expected (O/E) ratios, using Co-Occurring Defect Analysis (CODA). Results: Among 16, 442 cases with hypospadias and without known syndromes, 2, 084 (12.7%) had at least one additional defect. Many of the birth defect combinations within the highest adjusted O/E ratios included cardiac, musculoskeletal, and additional urogenital defects. For example, a top combination with an adjusted O/E of 139.0 included renal agenesis and dysgenesis, reduction defects of the upper limb, and other anomalies of upper limb (including shoulder girdle). High adjusted O/E ratios were also observed in combinations that included defects outside of the urogenital developmental field. For instance, the combination with the highest O/E ratio included buphthalmos, and congenital cataract and lens anomalies (adjusted O/E ratio: 192.9). Similar results were obtained when we restricted our analyses to cases with second- or third-degree hypospadias. Discussion: Many combinations in the top results were expected (e.g., multiple urogenital defects); however, some combinations with seemingly unrelated patterns of defects may suggest the presence of some etiologic mechanisms yet to be identified. Conclusion: In summary, this study described patterns of co-occurring defect combinations with hypospadias that can inform further study and may provide insights for screening and diagnostic practices.